Representación digital de la arquitectura y arquitectura de la representación digital - Martín Iglesias, Rodrigo A. (2016)
It is usually considered that the digital means of representation and production of the project give architects and designers the possibility to innovate and go beyond the limits of the discipline, thus giving them a power over forms previously unknown and practically within the reach of anyone. A promising panorama that generates a certain climate of expressive euphoria around digital practices, but that does not finish explaining how these innovations are possible or what the\noperational role played by the media is. While we do not deny that digital technologies have\nmade important contributions to project practices, this often leads to consequences that deserve\nattention and critical analysis. We are talking about the seduction of the tool by itself, succeeding in\nputting itself before architectural objectives, which provokes restrictions and inductions on design that go unnoticed by the neglected designer. Our research explores the ways in which these\ninfluences are generated and their consequent naturalization and aesthetization.